Crop residue burning: Challenges and sustainable solutions - Acharya, Kamlesh Kumar (Kurukshetra)
Long-term investments in infrastructure, raising awareness of sustainable practices, and making eco-friendly technologies more accessible will be keys to reducing stubble burning. Supporting biomass-based power plants with fiscal incentives can help create a market for crop residues, while establishing decentralized systems for their collection and sale will strengthen this supply chain. - Reproduced
Keywords: crops, seasonal patterns, crop residue burning